Stability Study of Parenteral N-Acetylcysteine, and Chemical Inhibition of Its Dimerization - Nicolas Primas; Guillaume Lano; Damien Brun; Christophe Curti; Marion Sallée; Emmanuelle Sampol-Manos; Edouard Lamy; Charleric Bornet; Stéphane Burtey; Patrice Vanelle (MDPI AG, 2023)
Parenteral N-acetylcysteine has a wide variety of clinical applications, but its use can be limited by a poor chemical stability. We managed to control parenteral N-acetylcysteine stability, and to study the influence of additives on the decrease of N-acetylcysteine degradation. First, an HPLC-UV dosing method of N-acetylcysteine and its main degradation product, a dimer, was validated and the stability without additive was studied. Then, the influence of several additives (ascorbic acid, sodium edetate, tocopherol and zinc) and of temperature on N-acetylcysteine dimerization was evaluated. Finally, the influence of zinc gluconate at different concentrations (administrable to patients) was investigated. Zinc gluconate at 62.5 µg·mL−1 allows the stabilization of 25 mg·mL−1 N-acetylcysteine solution for at least 8 days when stored at 5 ± 3 °C.